Negosiasi Budaya pada Amalgamasi (Studi Kasus Suku Bangsa Bugis dengan Minangkabau di Kelurahan Tagaraja) - Ramdesta, Andry; Syahrizal, Syahrizal; Anwar, Hairul (Sosial Budaya, 2023)
The Tagaraja Village shows the characteristics of a multicultural society with ethnic diversity including Malays, Bugis, Minangkabau, Javanese and others in one administrative area. Social relations that are established through amalgamation require that each family with a different cultural background negotiate with each other. The amalgamation that is the focus of this research is to find out the marriage system and how to negotiate marriages between the Bugis and Minangkabau ethnic groups who have differences in their marriage institutions. This study uses qualitative research with a case study approach. Data collection techniques were carried out through observation, interviews, documentation and literature studies. The results of the study show that the marriage procession is more dominant following the cultural peculiarities of the women's side, but lineage and inheritance rights are determined based on the agreement of the two families by calculating benefits from socio-cultural aspects.